Outcome Budget 2007-08 - Planning Commission (Planning Commission, 2007)
The document outlines various initiatives and projects aimed at modernizing office systems and enhancing spatial data infrastructure in India. It details the objectives, plan outlays, and achievements of several programs, including the development of a multi-layered Geographic Information System (GIS) for planning purposes, the establishment of a National Spatial Data Infrastructure, and the integration of digital topographic data. The report highlights the collaboration between various governmental agencies and research institutions to facilitate data sharing and improve decision-making processes at national, state, and district levels. Additionally, it discusses the training of personnel and the procurement of necessary technology to support these initiatives.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Spatial Data Infrastructure; Geographic Information System; Multi-Layer GIS; Planning Commission; Digital Topographic Data; Data Sharing; Training Programs; National Development; Research Institutions; Modernization Initiatives